(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2021)
The Yamuna River was sampled for 24 morphometric metrics and eight meristic countparameters for each fish species. There was a wide variation in length and weight for the Cyprnius carpio(14-18 cm), Mahseer (21–28 cm), Labeo rohita (20–26 cm), Xenontodon canceilia (17–25 cm), and otherspecies throughout the research period. There is a larger growth rate shown by the regressioncoefficient ’b.’ Although Xenontodon canceilia res was found to be the longest, it had the shortest pelvicfin length for standard length, whereas Cyprnius carpio was found to be the longest, with the shortestpelvic fin length for standard length.